The Effect of Vitamin D Supplementation on Disease Activity and Neutrophyl-Lymphocyte Count Ratio in Systemic Lupus Erythematosus Patients with Hypovitaminosis D : A Preliminary Study - Maslim, Y; Dewi, Sumartini; Oehadian, A; Wachjudi, Rachmat Gunadi (Indonesian Journal of Rheumatology, 2014)
Background : Previous studies showed a significant role of Vitamin D in modulating inflammation and immune abnormality in SLE. The correlation between vitamin D supplementation and SLE disease activity remains controversy. Neutrophyl-Lymphocyte count Ratio (NLCR) as an inflammation marker was significantly increased in SLE patients.Objective : To evaluate the effect of vitamin D supplementation on disease activity and neutrophyllypmhocyte count ratio (NLCR) in SLE patients with hypovitaminosis D.Methods : This is a pre-post test study without control group using a consecutive sampling method. SLE patients were enrolled from Rheumatology Clinic of HasanSadikin General Hospital from November 2013-March 2014. Subjects received vitamin D3 2000 IU/day for 3 months. Data was analyzed using Wilcoxon test.Results : We analyzed 28 subjects with 89,3% of vitamin D deficiency and 10,7% of vitamin D insufficiency, which converted to 25% of vitamin D deficiency, 32,1% vitamin D insufficiency and 42,9% normal vitamin D plasma level at the end of the study.After supplementation, Mexican Systemic Lupus Erythematosus Disease Activity Index (MEX-SLEDAI) and NLCR was significantly decreased (median 4(3-8) to 2(0-6) and median 2,95(1,17-7,27) to 2,28 (1,07-4,87), p<0,001, respectively). SLE organ involvement such as mucocutan, hematology and renal also high BMI (>23 kg/m2) were risks of hypovitaminosis D. Vitamin D supplementation increased mean 25(OH)D serum level by 164,7%, 46,7% decreased of MEX-SLEDAI, and 24,2% decreased of NLCR (p<0,001). Nine subjects (32,1%) achieved remission, 19 subjects (67,9%) atdisease persistence and no subjects experienced flare up after supplementation.Conclusion : The effects of vitamin D3 2000 IU/day supplementation for 3 months are reduced disease activity and NLCR in SLE patients with hypovitaminosisD. The role of NLCR as a simple inflammation marker in this pilot study needs further investigation.